Water and sanitation status relating to the poorest in Bangladesh - Akter, Nasima; Jakariya, Md. (BRAC Research and Evaluation Division (RED), 2020)
This study aimed to see the level of access to safe water and sanitation and discusses the knowledge on arsenic contamination in drinking water among the poorest in rural Bangladesh. This was a part of baseline survey for CFPR/TUP. Household survey method was used to collect information through structured questionnaire. The survey was conducted during July-September 2002 in Rangpur, Kurigram and Nilphamari districts. Variables considered were safe water and sanitation. Sources of drinking and cooking water, water quality with regard to arsenic, and knowledge on arsenic contamination were considered under safe water variable. Type, practice and ownership of latrine was considered under sanitation. Coverage of access to drinking water for SUP and NSUP of three study districts was above 96% which is similar to national rural water supply coverage (97%). Nevertheless, most of the households did not have their own tubewell and did not guarantee safe drinking water. It was also found that about 87% of the households drank water from tubewell those were not tested for arsenic contamination. Sanitation coverage of the study households was 5.4-9.4%, much lower than national sanitation coverage for rural area (30% or 4 1% including pit latrines). Lack of awareness along with unavailability of resources are some causes of poor water and sanitation coverage for the poorest. Raising awareness on safe drinking water and sanitation as well as ensuring safe drinking water and sanitation access to these districts need immediate attention to ensure and secure their healthy and sustainable livelihood.